Jurnal Pengaruh Jiwa Kewirausahaan dan Kemandirian Pribadi Terhadap Kinerja Usaha Kuliner Usaha Mikro Kecil (UMK) Kodam Street Food Surabaya - Anjani, Melia; Maduwinarti, Ayun; Mulyati, Diana Juni (Research Journal of Social Science and Economics, 2025)
Traders or entrepreneurs who are in the Kodam Brawijaya V Night Market have different levels of education. As a result, the insights possessed in entrepreneurship also vary as well as the independence in running a business.This type of research is field research, namely direct observation of the object under study in order to obtain relevant data. The method used in this research is to use quantitative analysis research methods. This means that in analyzing data using numbers to describe the character of a group. Using non-probability method with purposive sampling technique. The research data used in this study were collected by administering questionnaires to Surabaya Street Food Kodam MSEs using a Likert scale. Entrepreneurial Spirit has a partial influence on the Performance of Culinary Business Small and Medium Enterprises (MSEs) Kodam Street Food Surabaya. Personal Independence has a partial influence on the Culinary Business Performance of Small and Medium Enterprises (MSEs) Kodam Street Food Surabaya. Entrepreneurial Spirit and Personal Independence have a joint (simultaneous) effect on the Performance of Culinary Businesses of Small and Medium Enterprises (MSEs) Kodam Street Food Surabaya. In the entrepreneurial spirit variable in this study, it is better to increase the indicator of confidence in facing competition in the business market. In the Personal Independence variable in this study, it is better to increase the indicator of the ability to accept and be responsible for the consequences of every decision made in business. For business people, they should not be afraid to make decisions or take risks and be willing to face changes in the face of business competition.